2021
DOI: 10.1038/s41467-021-25192-4
|View full text |Cite
|
Sign up to set email alerts
|

Atomically dispersed Pb ionic sites in PbCdSe quantum dot gels enhance room-temperature NO2 sensing

Abstract: Atmospheric NO2 is of great concern due to its adverse effects on human health and the environment, motivating research on NO2 detection and remediation. Existing low-cost room-temperature NO2 sensors often suffer from low sensitivity at the ppb level or long recovery times, reflecting the trade-off between sensor response and recovery time. Here, we report an atomically dispersed metal ion strategy to address it. We discover that bimetallic PbCdSe quantum dot (QD) gels containing atomically dispersed Pb ionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 67 publications
2
42
0
Order By: Relevance
“…1G and H). 34 The Pb x Cd 1− x Se QDs displayed a similar surface morphology, crystallite size, and porosity to CdSe QD precursors. These Pb x Cd 1− x Se QDs exhibited an optimal combination of strong sensor response and fast recovery as a p-type semiconductor NO 2 sensor.…”
Section: Sascs Based On a Zero-dimensional Supportmentioning
confidence: 91%
See 1 more Smart Citation
“…1G and H). 34 The Pb x Cd 1− x Se QDs displayed a similar surface morphology, crystallite size, and porosity to CdSe QD precursors. These Pb x Cd 1− x Se QDs exhibited an optimal combination of strong sensor response and fast recovery as a p-type semiconductor NO 2 sensor.…”
Section: Sascs Based On a Zero-dimensional Supportmentioning
confidence: 91%
“…32,33 Most recently, researchers have devoted efforts to fabricating metal single-atom sites on these 0D materials for enhanced catalytic properties or exploiting quantum dots as special precursors for the synthesis of unique SASCs which are difficult to obtain from conventional reagents. [34][35][36][37][38] Li et al synthesized Co 1 /CQDs photocatalysts by pyrolyzing Co salts and vitamin B 12 composites (Fig. 1A-D).…”
Section: Sascs Based On a Zero-dimensional Supportmentioning
confidence: 99%
“…Subsequent reversal of the electrode potential led to disassembly . Similarly, Pb x Cd 1– x Se gels were formed via electrogelation of CdSe quantum dots followed by cation exchange and exhibited high NO 2 gas-sensing performance at an optimal ratio of Pb:Cd …”
Section: Controlled Aggregation By Progressive Destabilizationmentioning
confidence: 99%
“…27 Similarly, Pb x Cd 1−x Se gels were formed via electrogelation of CdSe quantum dots followed by cation exchange and exhibited high NO 2 gassensing performance at an optimal ratio of Pb:Cd. 28 The high structural stability of solvogels formed by progressive destabilization routes offers the opportunity to further process the gels into xerogels and aerogels (Figure 2b). 29,30 Aerogels are formed by removing the solvent in a solvogel via supercritical drying.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A new bimetallic Pb x Cd 1−x Se QD (QD) gel consisted of dispersed Pb ionic sites into CdSe crystal revealed a strong response and fast dynamics to NO 2 gas at 25 • C. The DFT calculation results indicated that Cd sites were responsible for the high NO 2 -sensing output because they offer remarkably higher charge transfer but comparable adsorption energy relative to the Pb sites. The Pb ionic sites acted as the transfer electron density to the neighboring Cd cations, causing them suitable electron donors to NO 2 gas, improving the gas sensor response [75].…”
Section: Pbcdse Qd Gas Sensormentioning
confidence: 99%